The other side of the disease. Three sanitarian crisis of Lima from 16th century to 21th century - Vásquez, Leandro (2023)
In the history of public health in Lima, there have been health crises that doubly condemned the city, due to the diseases and the poor response capacity of hospitals to deal with them. This article analyzes the transformation of hospital architecture to face these circumstances and reveals the periods of plague that have most unbalanced the capital’s medical system, from the Hospital Real de San Andrés (1552) against smallpox, the modern Hospital Dos de May (1875) against yellow fever and the East Lima Emergency Hospital (2018) against the coronavirus.